Concise encyclopedia of self-propagating high-temperature synthesis history, theory, technology, and products - Borovinskaya, Inna P.; Gromov, Alexander A.; Levashov, Evgeny A.; Maksimov, Yuri M.; Mukasyan, Alexander S.; Rogachev, Alexander S. (Amsterdam Elsevier, 2017)
The Concise Encyclopedia of Self-Propagating High-Temperature Synthesis: History, Theory, Technology, and Products helps students and scientists understand the fundamental concepts behind self-propagating high-temperature synthesis (SHS). SHS-based technologies provide valuable alterations to traditional methods of material fabrication, such as powder metallurgy, conventional and force sintering, casting, extrusion, high isostatic pressure sintering, and others. The book captures the whole spectrum of the chemistry, physics, reactions, materials, and processes of self-propagating high-temperature synthesis. This book is an indispensable resource not only to scientists working in the field of SHS, but also to researchers in multidisciplinary fields such as chemical engineering, metallurgy, material science, combustion, explosion, and the chemistry of solids.--Provided by publisher.
Keywords: Self-propagating high-temperature synthesis; Electronic books